PET Measures of D1, D2, and DAT Binding Are Associated With Heightened Tactile Responsivity in Rhesus Macaques: Implications for Sensory Processing Disorder - Schneider, Mary L.; Moore, Colleen F.; Ahlers, Elizabeth O.; Barnhart, Todd E.; Christian, Bradley T.; DeJesus, Onofre T.; Engle, Jonathan W.; Holden, James E.; Larson, Julie A.; Moirano, Jeffrey M.; Murali, Dhanabalan; Nickles, Robert J.; et al. (Frontiers in Integrative Neuroscience, 2019)
Sensory processing disorder (SPD), a developmental regulatory condition characterized by marked under- or over-responsivity to non-noxious sensory stimulation, is a common but poorly understood disorder that can profoundly affect mood, cognition, social behavior and adaptive life skills. Little is known about the etiology and neural underpinnings. Clinical research indicates that children with SPD show greater prevalence of difficulties in complex cognitive behavior including working memory, behavioral flexibility, and regulation of sensory and affective functions, which are related to prefrontal cortex (PFC), striatal, and midbrain regions. Neuroimaging may provide insight into mechanisms underlying SPD, and animal experiments provide important evidence that is not available in human studies. Rhesus monkeys (N = 73) were followed over a 20-year period from birth into old age. We focused on a single sensory modality, the tactile system, measured at 5-7 years, because of its critical importance for nourishment, attachment, and social reward in development. Positron emission tomography imaging was conducted at ages 12-18 years to quantify the availability of the D1 and D2 subtypes of the DA receptor (D1R and D2R), and the DA transporter (DAT). Heightened tactile responsivity was related to (a) elevated D1R in PFC overall, including lateral, ventrolateral, medial, anterior cingulate (aCg), frontopolar, and orbitofrontal (OFC) subregions, as well as nucleus accumbens (Acb), (b) reduced D2R in aCg, OFC, and substantia nigra / ventral tegmental area, and (c) elevated DAT in putamen. These findings suggest a mechanism by which DA pathways may be altered in SPD. These pathways are associated with reward processing and pain regulation, providing top-down regulation of sensory and affective processes. The balance between top-down cognitive control in the PFC-Acb pathway and bottom-up motivational function of the VTA-Acb-PFC pathway is critical for successful adaptive function. An imbalance in these two systems might explain DA-related symptoms in children with SPD, including reduced top-down regulatory function and exaggerated responsivity to stimuli. These results provide more direct evidence that SPD may involve altered DA receptor and transporter function in PFC, striatal, and midbrain regions. More work is needed to extend these results to humans.